Meister Eckhart: philosophy and mysticism - Soto Posada, Gonzalo (Estudios de Filosofía, 2012)
The article intends to show how the mysticism of Meister Eckhart is the immersion into the silent nothingness of God as empty fullness and full emptiness, in the desert of divine abundance of not being of God’s being, through compliance with the divine will as ascension that fulfills without fulfilling. It analyzes the life, work and thought of the Meister based on his texts, The Book of Divine Comfort, The Fruit of Nothingness, Eternal Life and Divine Knowledge, Echoes of Middle Age. The article ends with an epilogue in which it discusses “Mustard Grain” where the abundant desert of the silent nothingness of God and the many names without name is explained.